2019
DOI: 10.1039/c9cc03972d
|View full text |Cite
|
Sign up to set email alerts
|

A general diversity oriented synthesis of asymmetric double-decker shaped silsesquioxanes

Abstract: A strategically novel synthesis of nano-sized, asymmetrically functionalized double-decker shaped silsesquioxanes (DDSQ) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…However, significant symmetric byproduct waste would be generated and it required differences in polarity between the byproducts and the desired asymmetric material to be effectively separated. (Figure 11) [93]. Such an active protecting group could protect two silanols simultaneously, and it could be easily introduced and removed without affecting the B-POSS framework.…”
Section: Asymmetric Functionalization Of B-possmentioning
confidence: 99%
See 1 more Smart Citation
“…However, significant symmetric byproduct waste would be generated and it required differences in polarity between the byproducts and the desired asymmetric material to be effectively separated. (Figure 11) [93]. Such an active protecting group could protect two silanols simultaneously, and it could be easily introduced and removed without affecting the B-POSS framework.…”
Section: Asymmetric Functionalization Of B-possmentioning
confidence: 99%
“…The protocol is general and highly efficient for a wide range of asymmetrically functionalized B-POSSs. (Figure 11) [93]. Such an active protecting group could protect two silanols simultaneously, and it could be easily introduced and removed without affecting the B-POSS framework.…”
Section: Asymmetric Functionalization Of B-possmentioning
confidence: 99%
“…Octaarylsilsesquioxanes with reactive or non-reactive organic groups were synthesized from cyclotetrasiloxanetetraols and their sodium salts in the presence of ammonium catalysts [ 17 ]. Unsymmetrical silsesquioxane double-deckers of new types [ 17 , 18 , 19 , 20 , 21 , 22 ], the basket [ 23 ] and butterfly types [ 24 ], or siloxane cages were reported to be obtained by simple hydrolytic condensations of two cyclosiloxanes with an organomonosilane. They can be building blocks for diverse applications since materials based on them should have low dielectric constants and excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only a few studies on unsymmetrical silsesquioxane or siloxane cages have been reported because of the difficulty in obtaining a perfect Janus structure via a simple hydrolytic condensation of two organomonosilane precursors. Due to its unique chemical/physical properties related to type, number, and position of organic functional groups on a single molecule, the synthesis of asymmetrical structures has recently become an essential subject in chemistry [30,31,32,33,34,35]. Since the first report by the Laine group [30], to the most recent by the Kuroda group [31], on the synthesis of Janus cube octasilsesquioxane by the hydrolytic condensation of trimethoxy groups on cyclotetrasiloxanes rings, only our group has successfully synthesized a Janus cube from two different organic functional groups on cyclotetrasiloxane precursors [32].…”
Section: Introductionmentioning
confidence: 99%
“…This caused difficulty in controlling the synthesis, and purification required a vast difference in polarity between the product and the undesired compound [34]. One year later, this group succeeded in synthesizing an unsymmetrical DDSQ by using p -MeO-C 6 H 4 B(OH) 2 as the protecting group for each side of the reactive silanol group [35]. Developing an effective synthesis procedure for unsymmetrical DDSQ materials remains an interesting topic.…”
Section: Introductionmentioning
confidence: 99%